2013
DOI: 10.1002/jgrd.50578
|View full text |Cite
|
Sign up to set email alerts
|

Implications for Arctic amplification of changes in the strength of the water vapor feedback

Abstract: [1] One of the major climatic changes apparent over the Arctic Ocean has been the amplified rate at which air temperature has been increasing relative to the global mean. There are multiple factors which play roles in this amplification, including changes in sea ice/albedo, atmospheric circulation, clouds, and water vapor. We investigate the positive feedback on temperature caused by increasing downward longwave radiation flux (DLF) associated with increasing atmospheric precipitable water (PW). The Japanese 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(36 citation statements)
references
References 33 publications
1
34
0
1
Order By: Relevance
“…Together with the reduced water vapor path in the Pacific Sector of the Arctic Ocean, trends in the winter mean downward longwave radiative fluxes and T2m are smaller in this region compared with the Atlantic sector (Figures d and f). This signal is also robust and found in several reanalyses [ Serreze et al ., ; Ghatak and Miller , ; Lindsay et al ., ]. Serreze et al .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Together with the reduced water vapor path in the Pacific Sector of the Arctic Ocean, trends in the winter mean downward longwave radiative fluxes and T2m are smaller in this region compared with the Atlantic sector (Figures d and f). This signal is also robust and found in several reanalyses [ Serreze et al ., ; Ghatak and Miller , ; Lindsay et al ., ]. Serreze et al .…”
Section: Resultsmentioning
confidence: 97%
“…There is a dipole pattern during winter, with positive water vapor path trends in the Atlantic sector and negative trends in the Pacific Sector of the Arctic Ocean (Figure c). This is a robust pattern found in the ERA‐I, JRA‐55 MERRA‐2, and CFSR reanalyses, as well as long‐term radiosonde records from land‐based Arctic Stations [ Serreze et al ., ; Ghatak and Miller , ]. Together with the reduced water vapor path in the Pacific Sector of the Arctic Ocean, trends in the winter mean downward longwave radiative fluxes and T2m are smaller in this region compared with the Atlantic sector (Figures d and f).…”
Section: Resultsmentioning
confidence: 99%
“…A recent series of papers expressing similar conclusions indicates no summertime cloud response to sea ice loss that would offset, even partially, the sea ice albedo feedback [13,17,221,222]. Conversely, a fall and early-winter cloud response exists where slower sea ice growth (i.e., larger-than-average and longer-lasting areas of open water) contributes to enhanced LH flux, which moistens the lower troposphere [46,223], and results in increased cloud amount, cloud base height, and cloud water content [12,13,17,39,217,222]. Kurita [224] found that local sources are the dominant atmospheric water vapor supply for the formation of Arctic low clouds in late autumn and early winter.…”
Section: Cloudsmentioning
confidence: 83%
“…The Arctic amplification has attracted many researchers in recent decades [1][2][3][4] and the direct effect of the Arctic amplification is Arctic warming and the rapid melting of Arctic sea ice in all seasons [5,6]. Although the Arctic sea ice cover (SIC) is the least in late September, the significant decrease in winter sea ice and the more frequent extreme cold weather in mid-latitudes in winter make it necessary to focus on the winter Arctic SIC change and associated processes [7][8][9].…”
Section: Introductionmentioning
confidence: 99%